Does contract farming improve the technical efficiency of urban and peri-urban dairy farmers? Evidence from Nekemte city, Ethiopia - Mulatu, Gemechu (Nurture, 2024)
Purpose: The main objective of this study was to investigate the influence of contract farming on the technical efficiency of dairy farmers in urban and peri-urban areas, specifically in Nekemte City, Ethiopia. Design/Methodology/Approach: The research design employed to obtain the data was a cross-sectional study. For data analysis, both primary and secondary sources of information were gathered. A semi-structured questionnaire was used to collect primary data. A simple random sampling technique was followed to select 181 sample dairy farm producers in urban and peri-urban areas of Nekemte city. The data analysis methods that were employed included descriptive analysis, Cobb-Douglas stochastic frontier analysis, and the propensity score matching technique. Findings: According to the Cobb-Douglas stochastic frontier production function results, the most significant input in milk production is fodder, which has the biggest coefficient (= 0.353). The sum of the coefficients of all inputs is 0.512, and dairy farmers in the study area have been operating at decreasing returns to scale. The result of logistic regressions showed that the owner or manager's age, education, and experience are important factors that influence their decision to participate in urban dairy contract farming. The results of the propensity score matching technique showed that dairy farmers' technical efficiency increased by 0.150, or 21.52%, because of contract farming. Conclusion: The results of the study highlight that contract farming helps dairy farmers in urban and peri-urban areas become more technically efficient. Research Implications: The result of the study can serve as an input for policy formulation and serve as a stepping stone for other researchers.